Effect of Sugar, Salt, and Flavorings Addition on Temperature Changes and Specific Heat Capacity in Citric Acid, Acetic Acid, and Ascorbic Acid Solutions - Alfira Julian Pratiwi; Ekin Dwi Arif Kurniawan; Rafidah Almira Samosir; Mutia Ardila; Gioni Thesia Boru Simbolon; Afrilia Tria Ivanka; Muhammad Fadhli; Tetra Tasya Anggraini Butar; Eren Nazura; Moondra Zubir; Abd Hakim S (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study aims to evaluate the effect of the addition of additives in the form of sugar, salt, and flavorings on changes in temperature and type heat capacity in citric acid, acetic acid, and ascorbic acid solutions. The methodology used is a quantitative experimental approach with direct observation of temperature changes as well as calculation of enthalpy changes (ΔH) in various combinations of acidic and additive solutions. The results of the analysis showed that the types of additives exerted different effects on the thermal stability and heat capacity of each acidic solution. Sugars tend to provide the most optimal thermal stability with minimal fluctuations in ΔH change, while salts cause the greatest fluctuations. Flavorings show a more varied and inconsistent pattern of change. These findings provide in-depth insights into the thermal characteristics of organic acid solutions with additive modification, contributing to the development of applications in the fields of food, pharmaceutical, and applied chemistry education.